New antireflective coating materials containing a novel chromophore for KrF laser lithography - Ahn, K.-D.; Han, D.K.; Kim, J.-Y.; Ha, S.-H.; Lee, D.-Y.; Nam, J.-L. (Tokai University, 2001)
[No abstract available]
Keywords: flavone; isoflavone derivative; polymer; absorption; article; chromatophore; laser; lithography; material coating; structure analysis; surface property; technology